2020
DOI: 10.1103/physrevd.101.054029
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of charmoniumlike state X(3915) as χc0(2P)

Abstract: In this work, we seriously discuss whether X(3915) can be treated as a χ c0 (2P) state. Based on an unquenched quark model, we give the mass spectrum of the χ cJ (2P) states, where there are no free input parameters in our calculation. Our result shows that the mass gap between χ c0 (2P) and χ c2 (2P) can reach 13 MeV, which can reproduce the mass difference between Z(3930) and X(3915). Additionally, the calculated masses of χ c0 (2P) and χ c2 (2P) are consistent with experimental values of X(3915) and Z(3930)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 71 publications
2
25
0
Order By: Relevance
“…Moreover, in the D + D − channel, two charmonia χ c0 (3930) and χ c2 (3930) with J PC = 0 ++ and 2 ++ state, respectively, were found. Their masses and widths are determined to be [1,2] M χ c0 (3930) = 3.9238 ± 0.0015(stat) ± 0.0004(syst) GeV, Γ χ c0 (3930) = 17.4 ± 5.1(stat) ± 0.8(syst) MeV, M χ c2 (3930) = 3.927 ± 0.0024(stat) ± 0.0008(syst) GeV, Γ χ c2 (3930) = 34.2 ± 6.6(stat) ± 1.1(syst) MeV, which confirms the prediction from the Lanzhou group of small mass spliting and narrow width for the χ c0 (2P) and χ c2 (2P) states [3]. Especially, it is the first time to establish the χ c0 (2P) state in its open-charm decay channel, which also clarifies messy situation of the X(3915).…”
Section: Introductionsupporting
confidence: 83%
“…Moreover, in the D + D − channel, two charmonia χ c0 (3930) and χ c2 (3930) with J PC = 0 ++ and 2 ++ state, respectively, were found. Their masses and widths are determined to be [1,2] M χ c0 (3930) = 3.9238 ± 0.0015(stat) ± 0.0004(syst) GeV, Γ χ c0 (3930) = 17.4 ± 5.1(stat) ± 0.8(syst) MeV, M χ c2 (3930) = 3.927 ± 0.0024(stat) ± 0.0008(syst) GeV, Γ χ c2 (3930) = 34.2 ± 6.6(stat) ± 1.1(syst) MeV, which confirms the prediction from the Lanzhou group of small mass spliting and narrow width for the χ c0 (2P) and χ c2 (2P) states [3]. Especially, it is the first time to establish the χ c0 (2P) state in its open-charm decay channel, which also clarifies messy situation of the X(3915).…”
Section: Introductionsupporting
confidence: 83%
“…The χ c0 (2P) hypothesis for the X (3915) has been reinforced by new studies in Refs. [17,18]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [18] it is shown that the use of the unquenched quark model, where, in addition to the quark components, the meson-meson components are taken into account via loops with these intermediate states [19][20][21][22][23], provides an answer to the problems posed to the χ c0 (2P) hypothesis in Refs. [11,12], in particular the puzzle of the charmonium masses and the decay widths discussed above.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the decay of highly partial wave in the QPC model, the amplitude has a strong dependence on the shape of the wave function, because of the nodal effect, i. e. the β value has a great impact on the numerical result of the width [22].…”
Section: Introductionmentioning
confidence: 99%